Advokasi Hak Penyandang Disabilitas sebagai Gerakan Sosial Baru di Kota Semarang. - Arawindha, Ucca (PLD UIN Sunan Kalijaga, 2023)
This study aims to analyze the social action of Komunitas Sahabat Difabel (KSD) in advocating for the rights of persons with disabilities in Semarang. This research uses qualitative method. Data collection was conducted through interviews with disabled KSD members, KSD leaders, and the Semarang City Social Service. In addition, researchers also traced secondary data through the Semarang City BPS. The results of the research show that the social action carried out by Komunitas Sahabat Difabel (KSD) is a new social movement, because it carries humanitarian issues. In addition, in carrying out social actions, KSD uses the social media in providing education and disability awareness to the community. KSD also uses social networks in advocating for the rights of persons with disabilities in Semarang. The conclusion of this study is that KSD's social action in advocating the rights of persons with disabilities uses a strategy of mobilizing resources that are both tangible and intangible. It is hoped that this research can have a significant impact on increasing disability awareness and eliminating discrimination against disabilities.